THE IMPACT OF STRATEGIC MANAGEMENT ON ORGANIZATIONAL GROWTH AND DEVELOPMENT AMONG SELECTED MANUFACTURING FIRMS IN UAE - Umasekar, Dr Vijayakumar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The UAE has a dynamic economy that is always changing, and one of the main drivers of that growth is the manufacturing sector. Maintaining and driving growth in this industry requires an understanding of the function that strategic management plays. This research assesses the impact of strategic management on organizational growth and development among selected manufacturing firms in the UAE. In this study, a positivist research philosophy is used and a quantitative research method is followed. The data is collected through primary methods with the help of surveys. The sample size selected is 450 and the respondents are the employees working in selected manufacturing firms in the UAE. The purposive sampling is used in this study and the results show that product innovation, organizational culture, leadership, and competitive advantage have a significant impact on effective strategic management. Considering the growing emphasis on sustainable business practices worldwide, research could examine how manufacturing companies in the UAE incorporate environmentally conscious strategies into their overall growth and development plans.